Respostas
respondido por:
2
f(0) = 3 . 0 -4 f(-5) = 3 . (-5) -4 f(0,5) = 3 . 0,5 -4
f(0) = 0 -4 f(-5) = -15 -4 f(0,5) =1,5 - 4
f(0) = -4 f(-5) = 19 f(0,5) = -2,5
f(0) = 0 -4 f(-5) = -15 -4 f(0,5) =1,5 - 4
f(0) = -4 f(-5) = 19 f(0,5) = -2,5
respondido por:
2
f(x)=3x-4
f(0)=3.0-4
f(0)=0-4
f(0)=-4
f(-5)=3.(-5)-4
f(-5)=-15-4
f(-5)=-19
f(0,5)=3.0,5-4
f(0,5)=1,5-4
f(0,5)=-2,5
f(0)=3.0-4
f(0)=0-4
f(0)=-4
f(-5)=3.(-5)-4
f(-5)=-15-4
f(-5)=-19
f(0,5)=3.0,5-4
f(0,5)=1,5-4
f(0,5)=-2,5
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás